PENGEMBANGAN MODUL BERBASIS PEMBELAJARAN PEMAKNAAN PADA MATERI POKOK SISTEM PERIODIK UNSUR - Andhini Safira Amanda; Betty Holiwarni; Herdini Herdini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research aimed to develop and determine the feasibility of modules based on learning model of pemaknaan on the topic of periodic system of elements. This research method is research development (Research and Development) using a 4-D model that include phase of Define, Design, Development, Desseminate. Instruments that used in this research are validation sheets and respons of teacher and students sheet.. The module validation component includes aspects of content feasibility, language feasibility, presentation feasibility, graphic feasibility and pemaknaan aspects. The result of this research development show that module based on learning model of pemaknaan developed valid with the average score of module validation results by the validator team were 90.28% for content aspect, 93.33% for language aspect, 88.33% for presentation aspect, 87.5% for graphic aspect and 91.67% for pemaknaan aspect. The result of respons teacher and student of MAS Darel Hikmah Pekanbaru and SMAN 4 Pekanbaru about module in a row 86,54% and 97,88% with very good criteria.Keyword : Meaning Based Learning Modules, Periodic System Of Elements